Scientific and technical cooperation in earth sciences : memorandum of understanding between the United States of America and Iceland, signed at Reykjavik and Reston January 28 and April 9, 1982. - Iceland.; United States. 1982 Jan. 28. Treaties, etc. Iceland.; United States. Department of State. (Washington, D.C. : Dept. of State : For sale by the Supt. of Docs., U.S. G.P.O., 1985)
Mode of access: Internet.